Long Run Tendencies and Short Run Adjustments Between Official and Black Market Exchange Rates in MENA Countries - KULA, Ferit; ASLAN, Alper; OZTURK, Ilhan (International Journal of Economics and Financial Issues, 2014)
This study makes an attempt to examine the long run relationship between the official and black market exchange rates using monthly data for a sample of 13 Middle East and Northern African (MENA) countries from 1970 to 1998. Using the Pool Mean Group framework, the article provides evidence on proportional long run relationship between black and official market exchange rates in sample countries. The positive common long run official exchange rates (OEX) elasticity is statistically significant and slightly greater than one. The hypothesis of portfolio balance model is confirmed, implying that there exists a proportional long run equilibrium relationship between official exchange rates and black market exchange rates. However, the short run dynamics remain heterogeneous across countries. Keywords: Black market exchange rate; official exchange rates; Panel data; Panel cointegration; MENA countries JEL Classifications: C23; F31